2022
DOI: 10.3389/fonc.2022.1037794
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the tumor-suppressive activity of Maspin with p53 in retuning the epithelial homeostasis: A working hypothesis and applicable prospects

Abstract: Epithelial malignant transformation and tumorous development were believed to be closely associated with the loss of its microenvironment integrity and homeostasis. The tumor-suppressive molecules Maspin and p53 were demonstrated to play a crucial role in body epithelial and immune homeostasis. Downregulation of Maspin and mutation of p53 were frequently associated with malignant transformation and poor prognosis in various human cancers. In this review, we focused on summarizing the progress of the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…It was recently established that maspin is epigenetically regulated at the tissue level with variations depending on each histological type [9][10][11][12]. Epigenetic changes in maspin expression involve: cytosine (de)methylation; deacetylation of histones; decreased chromatin accessibility, causing loss of gene function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was recently established that maspin is epigenetically regulated at the tissue level with variations depending on each histological type [9][10][11][12]. Epigenetic changes in maspin expression involve: cytosine (de)methylation; deacetylation of histones; decreased chromatin accessibility, causing loss of gene function.…”
Section: Discussionmentioning
confidence: 99%
“…Maspin gene promoter methylation is involved in several cancers such as breast, thyroid, skin, and colon cancers and it was admitted that this is one of the most common mechanisms that causes loss of gene function. It is noteworthy that in somatic tissues, most CpG regions are methylated and tumor cells show global hypomethylation of DNA compared to their normal counterparts [9][10][11][12]. Hypomethylation is involved in the progression from premalignant to malignant and leads to the activation of genes involved in the development of cancer [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deng et al [1,7] demonstrated that the down-regulated expression of maspin and the up-regulated expression of uPA and MMP-7 play important roles in the invasion and metastasis of gastric carcinoma; accordingly, they can serve as biomarkers for the biopathological behavior of gastric tumors. Overall, maspin has proved to have a significative role in cancer diagnosis and prognosis [1,[8][9][10][11][12]. The expression of maspin was also used for the determination of the efficiency of treatment of gastric cancer, e.g., using fluorouracil-based chemotherapy [13].…”
Section: Introductionmentioning
confidence: 99%